Manajemen Corporate Social Responsibility (CSR) PT KAI (Persero) melalui Program Sampah Organik Black Soldier Flyes - Febriyanti, Fiet; Muhtadi, Asep Saeful; Rustandi, Ridwan (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
This study aims to determine the management process by PT KAI (Persero) CSR through the black soldier flyes organic waste The method used in this study is descriptive qualitative method using primary and secondary data sources, and data collection techniques used are observation, documentation, and in-depth interviews. The results of the study can be concluded that the CSR Unit of PT KAI has implemented CSR management, through; first, defining of problem by conducting research, analyzing environmental conditions and analyzing the direction of the central and local governments; second, planning and programming through submitting proposals, determining CSR program objectives, resources and finance, also setting targets; third, taking action by synergizing with the central government, local government and local residents, managing waste using the maggot method, and monitoring, as well as communication to small groups, conducting socialization and training, and communicating and disseminating information through social media; fourth, program evaluation through the form of monthly reports and evaluation as a measure for the success of the CSR program.